KARAKTERISASI DAN OPTIMASI EMULGEL NA DIKLOFENAK DENGAN METODE SIMPLEX LATTICE DESIGN - Turdiyanto, Totok; Iswandi, Iswandi; Kuncahyo, Ilham (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Diclofenac Na is an NSAID class of drugs that functions to treat pain and inflammation of rheumatoid arthritis, osteoarthritis or joint disease. The aim of this study is to investigate the effect of carbopol 940, HPMC K15M and propyleneglycol variations on the emulgel physical properties, carbopol concentration, HPMC, propyleneglycol to produce an optimum formula.The method used in this optimization is Simplex Lattice Design. The independent variables which include carbopol 490 , HPMC K15M , propylene glycol were then included in the expert design to obtain 16 runs. Each formula was tested for viscosity, spreadability, adhesion, pH, diffusivity and physical stability. Each parameter has a contour plot and by superimposing it can be determined the shaded area which is the area of ​​the optimum formula. The optimum formula was carried out using a one sample t-test with a 95% confidence level. Based on the results of superimposed superimposed graphic observations for the manufacture of diclofenac narium emulgel with test parameters including spreadability, viscosity, adhesion, PH, diffusion ability and stability test, the composition of Carbobol 940 0.5 - 1.22%, HPMC K-15M 3.24 - 3.77 Propylene glycol 5 - 6.26%. The results of the t-test showed that the Simplex Lattice Design equation in the formula showed results that were not significantly different, this shows the significance value of the results before treatment with treatment results > 0.05. This shows that the equation is valid and the stability test is stable.